Determination of penicillamine, tiopronin and glutathione in pharmaceutical formulations by kinetic spectrophotometry - Kukoc-Modun Lea; Biocic Maja; Radić Njegomir (Acta Pharmaceutica)
A novel and simple method for the determination of penicillamine (PEN), tiopronin (mercaptopropionyl glycine, MPG) and glutathione (GSH) in pharmaceutical formulations by kinetic spectrophotometry has been developed and validated. It is based on the redox reaction where the thiol compound (RSH) reduces CuII-neocuproine complex to CuI-neocuproine complex. The non-steady state signal of the formed CuI- neocuproine complex is measured at 458 nm. The initial rate and fixed time (at 1 min) methods were validated. The calibration graph was linear in the concentration range from 8.0 × 10‒7 to 8.0 × 10‒5 mol L−1 for the initial rate method and from 6.0 × 10‒7 to 6.0 × 10−5 mol L−1 for the fixed time method, with the detection limits of 2.4 × 10−7 and 1.4 × 10‒7 mol L−1, resp. Levels of PEN, MPG and GSH in pharmaceutical formulations were successfully assayed by both methods. The advantages of the presented methods include sensitivity, short analysis time, ease of application and low cost.